Development of a dual camera sit posture monitoring system - Cheah, Song Cheng (Nanyang Technological University, 2024)
This project aims to develop a lightweight, real-time, single-user-focused sit-posture monitoring system for the Final Year Project. The goal of this project is to address health concerns related to improper sitting habits in office settings. The uniqueness of this system design is the implementation of a dual-camera setup, which enables the system to capture the user’s posture from both front and side perspectives at the same time, allowing it to analyze the frames and estimate the sitting posture immediately.